Project cool guide to XML for Web designers - Martin, Teresa A., 1961- (John Wiley, 1999)
Teresa A. Martin gets you up to speed on what XML is, how it works, how it fits in with other web design and development tools, and how, when, and why to incorporate it into your web site. Project Cool Guide to XML for Web Designers is the only XML guide geared specifically to the needs of webmasters and designers, and offers clear step-by-step guidance for integrating the XML process - from DTDs, parsing, and assigning style data to displaying a page in web browsers.